World of civil aviation 1994-1997 (IACO MontrealCA, 1995)
Reviews the main events in or affecting international civil aviation in 1994. Analyses trends in the world economy and the air transport industry and presents global forecasts of airline scheduled passenger traffic through to 1997. Reviews, on a region-by-region basis, the year 1994 and gives prospects through to 1997.
DC